2022
DOI: 10.3390/ma15227898
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Bioactive Glass-Modified Calcium Phosphate/Calcium Sulfate Biphasic Porous Self-Curing Bone Repair Materials and Preliminary Research on Their Osteogenic Effect

Abstract: In this study, calcium phosphate (CP)/calcium sulfate biphasic bone repair materials were modified with bioactive-glass (BG) to construct a self-curing bone repair material. Tetracalcium phosphate, calcium hydrogen phosphate dihydrate, and calcium sulfate hemihydrate (CSH) with different BG ratios and phosphate solution were reacted to prepare a porous self-curing bone repair material (CP/CSH/BG). The solidification time was about 12 min, and the material was morphologically stable in 24 h. The porosity was ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…High wetting ratios can increase the setting time to unacceptable values and can cause the washing away of the unset cement if exposed to an aqueous environment. Studies have shown that a curing time of 15–20 min is appropriate after delivering CPC slurry to the repair sites for bone defect rehabilitation [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High wetting ratios can increase the setting time to unacceptable values and can cause the washing away of the unset cement if exposed to an aqueous environment. Studies have shown that a curing time of 15–20 min is appropriate after delivering CPC slurry to the repair sites for bone defect rehabilitation [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…High wetting ratios can increase the setting time to unacceptable values and can cause the washing away of the unset cement if exposed to an aqueous environment. Studies have shown that a curing time of 15-20 min is appropriate after delivering CPC slurry to the repair sites for bone defect rehabilitation [27]. Working time is defined as the time during which no mutual adhesion, and setting time is when the mixed slurry exhibits a certain strength after initial hardening.…”
Section: Working Time For Operation and Setting Time For Adhesion And...mentioning
confidence: 99%
“…However, its poor resorbability hinders the formation of new bone and obstructs bone healing ( 14 , 15 ), and calcium phosphate cement hardly induces the formation of a bone-like HA layer in vitro and in vivo ( 16 ) Several previous studies have reported that tricalcium phosphate resorbs over a period lasting between 6 and 18 months ( 10 , 17 ), whereas hydroxyapatite can resorb over a period ranging from 6 months to 10 years ( 11 ). Bioactive glasses possess excellent osteoconductivity and the ability to stimulate bone formation, while their high brittleness and poor resorbability limit their application in load-bearing sites ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, bone substitute materials have been an area of intense research interest, and a variety of materials have been used to fill bone defects and promote bone regeneration, including autografts, allografts, calcium phosphate, bioglass, calcium sulfate, and their compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, each bone substitute has its own unique advantages and disadvantages (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%